2013
DOI: 10.1039/c3cp51217g
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of iodine oxide particle formation

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 53 publications
(84 reference statements)
6
83
0
Order By: Relevance
“…Prominent featureless absorption bands of I x O y species have been experimentally observed in the UV region (Bloss et al, 2001;Gómez Martín et al, 2005;. The photolysis thresholds of the iodine oxides are mostly in the near-infrared region (Gálvez et al, 2013).…”
Section: Absorption Cross-sections Of I X O Ymentioning
confidence: 93%
See 3 more Smart Citations
“…Prominent featureless absorption bands of I x O y species have been experimentally observed in the UV region (Bloss et al, 2001;Gómez Martín et al, 2005;. The photolysis thresholds of the iodine oxides are mostly in the near-infrared region (Gálvez et al, 2013).…”
Section: Absorption Cross-sections Of I X O Ymentioning
confidence: 93%
“…Based on the kinetic behaviour of the absorption spectra observed in the laboratory, tentative spectral assignments and estimation of the corresponding absorption cross-section have been reported. While Bloss et al (2001) assigned the broadband absorption appearing under the IO spectrum to a single species (I 2 O 2 ), Gómez Martín et al ( , 2007 obtained evidence of the same band resulting from an overlap of at least two different iodine oxides (I 2 O 2 and I 2 O 3 ). Here, in order to calculate atmospheric photolysis rates, we adopt for these two species the spectra extracted and scaled to absolute absorption cross-section by Gómez Martín et al (2005) (Fig.…”
Section: Absorption Cross-sections Of I X O Ymentioning
confidence: 99%
See 2 more Smart Citations
“…O 3 can directly react with volatile organic compounds or indirectly affect sulfuric acid formation via hydroxyl and hydroperoxy radicals (Berndt et al, 2010;Gómez Martín et al, 2013;Sorribas et al, 2015;Guo et al, 2012), and thus O 3 in the atmosphere may theoretically play a role in NPF. Previous research showed that elevated O 3 concentration was beneficial to the occurrence of NPF events Guo et al, 2012;Zhang et al, 2016;Huang et al, 2016), and our results did not directly show a similar phenomenon.…”
Section: Condensation Sinks and Sources Of Npfmentioning
confidence: 99%